Z etymologii polskiej (4): sowity - Fałowski , Adam (Slavia Occidentalis, 2024)
In modern Polish, the adjective sowity belongs to the book style and has the meaning ‘abundant, ample, rich’, e.g. ample time. The subject of the article is a chronological, semantic and etymological analysis of the word. Much attention has been devoted to study its origin and a formal-semantic evolution in Polish as well as some other Slavic languages (Ukrainian, Belarusian, Lithuanian) which have proved not entirely convincing. Thus, everything seems to indicate that the Polish adjective sowity is a native formation. It was coined from the base of the verb *sovati, *sujǫ ‘to slip, push in, press in, cram in, etc.’. with the help of the -it(y) suffix. Its original meaning was ‘slipped in, pushed in, pressed in, crammed in, etc.’. Consequently, the meaning of the Old Polish combination of a sowity coat ‘lined with cloth or fur, literally: stuffed, lined with something’ becomes perfectly clear. The meaning further developed as follows: ‘double, twofold, dual, amounting to the double amount, Latin duplex, duplus’ > ‘generous, abundant, rich, lavish, abundant with excess, measured with usury’ and others. It should be noted that when it comes to the latter, sowity very much resembles the adjective (from the origin of the past participle of the past tense from suć < *suti, *sъpǫ ‘to poor’) suty ‘abundant, rich, prosperous’ and ‘generous, abundant, lordly’, e.g. abundant payment, abundant remuneration, ‘prosperous; magnificent, splendid’, e.g. rich and abundant dress, rich attire. It is hard to resist the impression that sowity and suty influenced each other semantically, cf. above all the common meaning ‘generous, abundant, rich, prosperous, generous’.